Examining the Relationship between Digital Obesity, Digital Addiction, Desire for Self-Control, and Academic Achievement among University Students - Özbay, Özkan (Addicta: The Turkish Journal on Addictions, 2025)
This study aimed to examine the interrelated roles of digital obesity, digital addiction, desire for selfcontrol, and academic achievement among university students. A cross-sectional design was employed with 500 undergraduate students recruited through convenience sampling. Data were collected using the Personal Information Form, Digital Obesity Scale, Digital Addiction Scale, and Desire for Self-Control Scale. Descriptive analyses were followed by Pearson correlation and multiple linear regression analyses. Results revealed a strong positive correlation between digital obesity and digital addiction (r = 0.81, p < .01). Moreover, digital obesity was negatively associated with grade point average (r = −0.33, p < .01) and with desire for self-control (r = −0.13, p < .01). Digital addiction also showed negative correlations with grade point average (r = −0.33, p < .01) and desire for self-control (r = −0.22, p < .01). The regression model explained 68.4% of the variance in digital addiction (R2 = 0.684, F = 178.224, p < .001), with digital obesity emerging as the strongest predictor (β = 0.765, p < .001). Daily internet usage had a significant positive effect (β = 0.057, p = .048), whereas desire for self-control negatively predicted addiction (β = −0.097, p < .001). The findings underscore digital obesity as a central risk factor fostering addictive behaviors, while self-control motivation operates as a protective mechanism. Importantly, the integration of digital obesity, self-control motivation, and academic performance highlights the broader academic and psychological implications of digital risks. Interventions for university students should therefore focus not only on reducing screen time but also on enhancing digital literacy, strengthening self-control skills, and supporting academic success.
Keywords: Academic performance; digital addiction; digital obesity; self-control; university students